The Rolling Motion Light Painting Blur as the Jouvenile’s New Innovation Phenomenon in 2020’s: Lukisan Cahaya Gerak Bergulir Kabur Sebagai Fenomena Inovasi Baru Jouvenile di Tahun 2020 - Soeharno, Ageng; Wicaksono, Itok (MEDIAKOM, 2024)
Photography is a word from the Greek "photos" (light) and "graphos" (writing), meaning "writing with light" (. Lynch-Johnt, B. A., & Perkins, Michelle.; 2008). According to the International Monetary Fund, the Covid-19 pandemic was the reason behind the global recession that resulted in rising rates of poverty and unemployment across all nations. As for the alternative to restoring economic institutions in each nation, it is economic recovery by the reinforcement of economic stimulus through local techniques (Arianto, B. 2021). The writing of this research theme is considered important because of the importance of the new photography result that is generated by this technique. The research aims to find new things to ask about cases that arise in the problems, namely:Generating the best result on rolling motion light painting blur photography, and The best speed of rolling motion that must be taken by the photographer to generate the best result on rolling motion light painting blur photography. Qualitative research is grounded on values that emphasize the significance of individuals' subjective experiences and meaning-making processes, as well as the acquisition of a deep understanding (i.e., specific details from a small sample). In general, qualitative research is acceptable when exploring, describing, or explaining is your main goal (Leavy, Patricia: 2017). The movement taken by the researcher to get the results desired by the researcher is a rotating movement, where the camera is held by both hands with the arms straightened forward, so that the camera grip is held tightly, where this tight grip will impact the camera so that it does not experience significant shaking The speed used to rotate the camera, especially in the last test, is 2 seconds, while the remaining 2 seconds are used to focus the camera on the talent, so that as far as possible the 2 seconds are used to rotate the camera properly and without significant shaking.